Perspectives of vaccinators on the factors affecting uptake of meningococcal ACWY vaccine amongst school leavers in London. (November 2018) - Seok, J.; Heffernan, C.; Mounier-Jack, S.; Chantler, T.
Abstract: Objectives: Uptake of meningococcal ACWY (Men ACWY) vaccine amongst school leavers is suboptimal in London (9.9% compared to 17.4% nationally in 2015/16). This study explores service delivery barriers and elicits insights from general practice staff on their interaction with this cohort. The purpose was to inform the National Health Service England (London) public health commissioning team's strategy to improve Men ACWY vaccination uptake in London. Study design: Qualitative semi-structured interviews study. Methods: Purposive sampling of practice nurses from three general practices from each of the three London clinical commissioning group areas (Barnet, Camden and Newham) with the largest numbers of 18–20 year old registered patients. Participants were recruited through their practice managers. A thematic analysis approach was used. Results: A total of ten interviews were conducted between June and August 2017. Five themes were identified: (1) Nurses unsupported by practice systems; (2) difficulty getting school leavers into the practice; (3) confused messaging; (4) reliance on parental responsibility for health; and (5) perception of complacency amongst adolescents. Conclusion: Little is known about the service factors that impede uptake of adolescent vaccinations. This exploratory study suggests that existing programmatic mechanisms for delivering the Men ACWY catch-up programme were not adequate. The number of adolescent vaccinations offered has increased in the UK in the last five years and is likely to continue. Although the findings need to be further extrapolated in quantitative research, general practice staff need more systematic guidance on their role and how they can support vaccine decision-making in later adolescence. Highlights: Little is known about the service factors that impede uptake of adolescent vaccinations. We interviewed practice nurses on the low uptake of meningococcal ACWY vaccination in their practices. Nurses reported their work was unsupported by practice systems. There was difficulty getting adolescents into practices. Older adolescents rely on parental responsibility for their health.